Fluorogenic substrates for the detection of saliva. (December 2017) - Gooch, James; Chua, Chang Rong; Abbate, Vincenzo; Frascione, Nunzianda
Abstract: The potential of fluorogenic substrates to detect and identify human saliva in situ was first explored using commercially available substrate Boc-VPR-AMC. The substrate was applied to a range of saliva dilutions deposited on glass microscope slides. A positive fluorescence response was observed immediately after application against each deposit up to a 1:8 dilution. In an attempt to improve assay sensitivity, a novel substrate Ac-VPR-Rho110-Ac, utilising a Rhodamine-110 fluorophore, was prepared using a solid-phase peptide synthesis protocol previously reported by our research group. Application of Ac-VPR-Rho110-Ac to saliva deposits demonstrated a successful increase in assay sensitivity limits, allowing stains of up to 1 in 128 dilution to be detected.